Exploring the Challenges of Malay-muslim Single Fathers - Jamayah Saili; Muhamad Nor Syakirin Bin Muhamad Sa’ad (RedWhite Press, 2021)
Despite the relatively high degree of research among single mothers in Malaysia, there remains lack of research on issues and challenges faced by the single fathers. Fathers are by far the increasing sub group in the community, yet little is known about single fathers’ experience. The rise in the number of divorce is seen as being among the most significant changes to have affected single parenting. Drawing on in-depth qualitative interviews with five Malay Muslim single fathers, a cultural definition of being single father, further work is needed to consider the viewpoints on being single father which may have specific meanings in comparisons with other context and culture. The analysis of this in-depth interview yielded that the single fathers’ experience was marked by challenges, coping strategies and support system.